2005
DOI: 10.1177/10983007050070040501
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Effect of Teacher Positive and Neutral Affect on Task Performance of Students With Significant Disabilities

Abstract: The study uses an alternating treatment design to evaluate the functional effect of teacher's affect on students' task performance. Tradition in special education holds that teachers should engage students using positive and enthusiastic affect for task presentations and praise. To test this assumption, we compared two affective conditions. Three teachers working with a total of 4 elementary-age students with severe disabilities presented discrete trial tasks in neighborhood public school settings. The teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…However, it is important to consider that the strong social motivation observed in this population may serve as a distractor as well [Wishart, 1996;Fidler, 2006; see discussion below]. There is also some evidence that, because of strengths in early social relatedness in this population, affective cues put forth by a teacher or interventionist can impact learning and motivation in a particularly pronounced way [Park et al, 2005]. It may also be important for educators to be mindful of potential changes in mood and social engagement as children with Down syndrome transition into adolescence, and perhaps adopt modified strategies as these behavioral changes become evident [Dykens et al, 2002].…”
Section: Social-emotional Functioningmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it is important to consider that the strong social motivation observed in this population may serve as a distractor as well [Wishart, 1996;Fidler, 2006; see discussion below]. There is also some evidence that, because of strengths in early social relatedness in this population, affective cues put forth by a teacher or interventionist can impact learning and motivation in a particularly pronounced way [Park et al, 2005]. It may also be important for educators to be mindful of potential changes in mood and social engagement as children with Down syndrome transition into adolescence, and perhaps adopt modified strategies as these behavioral changes become evident [Dykens et al, 2002].…”
Section: Social-emotional Functioningmentioning
confidence: 96%
“…It is true that relative to other disorders, greater research emphasis has been placed on identifying educational strategies that might improve outcomes in Down syndrome. Some of these recent approaches are informed by and specifically target aspects of the Down syndrome behavioral phenotype [Laws et al, 1996;Kennedy and Flynn, 2003;Iarocci et al, 2006;van Bysterveldt et al, 2006], and others do not [Garcia and Conte, 2004;Park et al, 2005;Trent et al, 2005]. Those existing syndrome-based recommendations may be potentially quite useful, but lack empirical validation [Alton, 1998;Fidler, 2005].…”
mentioning
confidence: 97%
“…Consistent with previous research, the current study demonstrated that preferred stimuli incorporated into otherwise nonpreferred tasks can increase compliance (Cooper et al, 1992;Gardner et al, 2009; and positive affect (Dunlap et al, 1984;Lancioni et al, 2004;Park et al, 2005). Additionally, the current study demonstrated that empirically validated preference assessments can be implemented efficiently to achieve these results.…”
Section: Contributions To Preference Assessment Literaturesupporting
confidence: 88%
“…The results showed an increase in both engagement and indices of happiness when the preferred stimuli were activated concurrently with the exercise equipment (Lancioni et al, 2004). Park, Singer, and Gibson (2005) extended the research on indices of happiness by evaluating preferred attention rather than preferred tangible items as the independent variable. Specifically, they studied the role of quality of attention in increasing task engagement and indices of happiness with elementary-aged students with severe disabilities.…”
Section: Lancioni Et Al Connected Microswitches To Preferred Items Amentioning
confidence: 83%
See 1 more Smart Citation